2010
DOI: 10.1055/s-0030-1253420
|View full text |Cite
|
Sign up to set email alerts
|

Medical Treatment of Hyperthyroidism: State of the Art

Abstract: Methimazole (MMI) and propylthiouracil (PTU) are the main antithyroid drugs used for hyperthyroidism. They inhibit the synthesis of thyroid hormone at various levels and are used as the primary treatment for hyperthyroidism or as a preparation before radioiodine therapy or thyroidectomy. MMI is the drug of choice because of its widespread availability, longer half-life and small number of severe side effects. Drugs of second choice are potassium perchlorate, beta blockers, iodine, lithium carbonate and glucoco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
31
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 69 publications
3
31
0
3
Order By: Relevance
“…Hyperthyroidism (Graves' disease) is an endocrine disorder with about 2% prevalence in females and 0.2% in males (1-3) and an estimated annual incidence rate of 20 per 100,000 population (2,3). However, in regions without iodine deficiency, Graves' disease is the most common cause of hyperthyroidism, constitutes about 80% of hyperthyroidism cases, while hyperfunctioning autonomous adenomas are the most common cause in regions facing iodine deficiency (2,3).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hyperthyroidism (Graves' disease) is an endocrine disorder with about 2% prevalence in females and 0.2% in males (1-3) and an estimated annual incidence rate of 20 per 100,000 population (2,3). However, in regions without iodine deficiency, Graves' disease is the most common cause of hyperthyroidism, constitutes about 80% of hyperthyroidism cases, while hyperfunctioning autonomous adenomas are the most common cause in regions facing iodine deficiency (2,3).…”
Section: Introductionmentioning
confidence: 99%
“…However, in regions without iodine deficiency, Graves' disease is the most common cause of hyperthyroidism, constitutes about 80% of hyperthyroidism cases, while hyperfunctioning autonomous adenomas are the most common cause in regions facing iodine deficiency (2,3). Thyroid function disorders are among the most common endocrine diseases (4,5).…”
Section: Introductionmentioning
confidence: 99%
“…Los fármacos antitiroideos son la base del tratamiento del hipertiroidismo, especialmente en mujeres jóvenes con enfermedad de Graves (EG) (1) . En nuestro país, de este grupo de medicamentos, solo se dispone del metimazol (MMI), el cual está asociado a diversos eventos adversos, la mayoría de los cuales son leves, transitorios y dependientes de la dosis utilizada.…”
Section: Reporte De Caso Introducciónunclassified
“…Shergy WJ et al reported a case of a patient with polymyositis and high CK levels after PTU treatment for hyperthyroidism but the authors failed to distinguish if the elevation CK was related to drug effect of PTU or polymyositis. The patients symptoms resolved after withdrawal of PTU and treatment with prednisone and metotrexate [2]. Suzuki et al reported 4 cases of adult patients with Graves' disease and an abnormal increase in serum CK concentrations during treatment with thionamides.…”
mentioning
confidence: 98%
“…Minor side efects can resolve spontaneously; in case of persistence, the administered thionamide can be replaced by another available drug. Major side effects are agranulocytosis, hepatotoxicity, aplastic anemia and vasculitis, and occur in approximately 0.2-0.5 % of the cases [2]. Myalgia is a rare side effect these drugs.…”
mentioning
confidence: 99%